The Superconducting Magnetoresistance Effect in Ni80Fe20-Nb-Ni80Fe20 and Co-Nb-Co Trilayers: Requisites for Tailoring its Magnitude - Stamopoulos, D.; Aristomenopoulou, E.; Manios, E.; Niarchos, D. (JOURNAL OF SUPERCONDUCTIVITY AND NOVEL MAGNETISM, 2013)
The superconducting magnetoresistance effect (SMRE) observed in trilayers (TLs) consisting of a superconducting (SC) Nb interlayer and two outer ferromagnetic (FM) Ni80Fe20 and Co layers is studied. We observed that the SMRE exhibits a pronounced magnitude (R-max - R-min)/R-nor of order 45 % and 86 % for the NiFe-based and Co-based TLs, respectively. For the NiFe-based TLs, the dynamic transport behavior of the observed SMRE is presented through detailed I-V characteristics that exhibit a nonlinear character even extremely close to the critical temperature, T-c(SC). Also, the detailed evolution of the longitudinal and transverse components of the TL magnetization from close to well below T-c(SC) is presented. For the Co-based TLs, the obtained magnetization and transport data justify that a strict requisite for the observation of a pronounced SMRE across T-c(SC) is that the coercivities of the FM layers should be similar. The combined data on the NiFe-based and Co-based TLs show that across the superconducting transition the SMRE is influenced by out-of-plane stray-fields, attaining pronounced values when the respective coercive fields coincide, thus enabling the transverse magnetic coupling of the outer FM layers through the SC interlayer.